THE ROLE OF CUSTOMER SATISFACTION IN MEDIATING THE INFLUENCE OF SERVICE QUALITY ON PARTICIPANT LOYALTY (CASE STUDY AT THE SIDRAP BRANCH OF THE EMPLOYMENT SOCIAL SECURITY ADMINISTRATOR AGENCY) - Syurya, Rahmini; Semmaila, Baharuddin; Ramlawati, Ramlawati (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the effect of service quality on customer satisfaction. To analyze the effect of service quality on participant loyalty. To analyze the effect of customer satisfaction on participant loyalty. To analyze the effect of customer satisfaction on the mediation of service quality on participant loyalty at the Sidrap Branch of BPJS Ketenagakerjaan. Data collection techniques used were questionnaires using path analysis. The results show that service quality has a positive and significant effect on customer satisfaction. Service quality has a positive and significant effect on participant loyalty at the Sidrap Branch of BPJS Ketenagakerjaan. Customer satisfaction has a positive and significant effect on participant loyalty at the Sidrap Branch of BPJS Ketenagakerjaan. Customer satisfaction can mediate the effect of service quality on participant loyalty at the Sidrap Branch of BPJS Ketenagakerjaan.